Combined and individual applications of ozonation and microwave treatment for waste activated sludge solubilization and nutrient release - SEMERCİ, NESLİHAN (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2019)
This study focused on the separate and combined applications of ozonation and microwave treatment to enhance the phosphorus and ammonia release from waste activated sludge. Twenty-six batch experiments were run with or without acidic (pH 2) and alkaline (pH 10) pretreatments and different ozone dosages. Also, microwave post treatments were applied to enhance phosphorus release efficiency. Results showed that ozonation is an effective technology for solubilization and release without any pre or post-treatment, reactive phosphorus content increased from 1.9 to 3.6 mg PO4-P/g MLSSin (89.5% increase) with 19.4% COD release. Alkaline pretreatment enhanced sludge solubilization and phosphorus release at most (23.9% COD release and 152.6% PO4-P increase); however, decreases in ammonia, calcium and magnesium concentrations pointed out a loss of a part of released phosphorus, due to struvite or apatite precipitation. Acidic pretreatment reduced the sludge solubilization during ozonation (10% COD release) but prevented the uncontrolled precipitation and enhanced the phosphorus release (115.8% PO4-P increase). For microwave treatment, acid pretreated sludge showed higher release than alkaline pretreated or neutral sludge. Among different process combinations, acid pretreatment/ozonation/microwave experiments have shown the highest sludge solubilization and nutrient release (48% COD release and 579% PO4-P increase); however, the difference between acid pretreatment/microwave and acid pretreatment/ozonation/microwave was not significant in terms of phosphorus release (479% PO4-P increase, p = 0.082). Thus, pH 2/microwave may be a cost-effective and feasible alternative for nutrient recovery from waste sludge. For struvite precipitation, pH 8.5 were determined as optimum level. Also using fine struvite particles as seed increased struvite precipitation efficiency.
Keywords: Nutrient recovery; Sludge management; Sludge reduction; Ozonation; Microwave treatment; ADVANCED OXIDATION PROCESS; SEWAGE-SLUDGE; EXCESS SLUDGE; PHOSPHORUS RECOVERY; STRUVITE CRYSTALLIZATION; ANAEROBIC-DIGESTION; PILOT-SCALE; PRETREATMENT; DISINTEGRATION; REDUCTION